Kimura Disease Manifesting as Synchronous Bilateral Parotid Swelling in a Young Middle-Eastern Patient - Fatemah Faras; Fawaz Abo-Alhassan; Khalid Al-Sebeih; Jassem Bastaki (Case Reports in Surgery)
Kimura disease is a rare, benign, chronic inflammatory swelling of the subcutaneous tissue, lymph nodes, and glandular tissue. Characteristic features of the disease include, but not limited to, painless subcutaneous head and neck swelling, blood and tissue eosinophilia, and markedly elevated immunoglobulin E (IgE) levels. Herein, we report a rare case of Kimura disease manifesting as synchronous bilateral parotid swelling of 12 years duration in a 33-year-old Middle-Eastern man. To our knowledge only few cases have been reported in the literature involving bilateral parotid glands, and this is the first case to be reported in the Middle East.